The limits of behavioral nudges to increase youth turnout: Experimental evidence from two French elections - Romaniuc, Rustam; Guido, Andrea; Baudry, Pierre; Bazart, Cécile; Berger, Loïc; Berlin, Noémi; Bonein, Aurélie; Bouhlel, Imen; My, Kene Boun; Chessa, Michela; Crosetto, Paolo; Dagorn, Etienne; et al. (Journal of economic behavior & organization, 2025)
There is a significant gap in turnout between young people and older voters. The failure to instill a voting habit at an early age may have long term consequences in terms of future political participation as well as on other civic behaviors. Using a pre-registered online experiment with 3790 subjects, we implemented behavioral interventions aiming to stimulate youth turnout in the 2022 French presidential election. We rely on an innovative incentive scheme to measure their consequences on (self-reported) actual voting behavior. We also provide evidence on the effect of one behavioral intervention on youth turnout in a less salient election, the French legislative election that took place two months after the Presidential one. The results from the two experiments show the absence of any differences in turnout between the baseline and the treatment conditions. We investigate several mechanisms that can explain our results.